Diagnosing Sporadic Creutzfeldt-Jakob Disease in a Patient with a Suspected Status Epilepticus in the Intensive Care Unit - Harm J. van der Horn; Peter H. Egbers; Michaël A. Kuiper; Wouter J. Schuiling (Case Reports in Neurological Medicine)
Objective. Several tests are available in the diagnostics of sporadic Creutzfeldt-Jakob disease (sCJD); however, none of these is conclusive. We review the values of these tests, from an intensive care unit (ICU) perspective. Methods. Case report and review of the literature. Results. A 53-year-old woman initially presenting with psychiatric symptoms developed myoclonus and was admitted 1 month later to the ICU with a suspected nonconvulsive status epilepticus and respiratory insufficiency, probably due to extensive antiepileptic drug therapy. Typical MRI and EEG findings and a positive 14-3-3 protein led to the diagnosis of sCJD. All treatments were terminated, and autopsy confirmed sCJD. Conclusions. Clinical signs combined with MRI, EEG, and 14-3-3 and/or tau protein determination might be sufficient to diagnose or exclude sCJD and may therefore prevent the application of unnecessary diagnostic tests.